Intraneural sensory feedback restores grip force control and motor coordination while using a prosthetic hand. (27th February 2019) - Clemente, Francesco; Valle, Giacomo; Controzzi, Marco; Strauss, Ivo; Iberite, Francesco; Stieglitz, Thomas; Granata, Giuseppe; Rossini, Paolo M; Petrini, Francesco; Micera, Silvestro; Cipriani, Christian
Abstract: Objective . Tactile afferents in the human hand provide fundamental information about hand-environment interactions, which is used by the brain to adapt the motor output to the physical properties of the object being manipulated. A hand amputation disrupts both afferent and efferent pathways from/to the hand, completely invalidating the individual's motor repertoire. Although motor functions may be partially recovered by using a myoelectric prosthesis, providing functionally effective sensory feedback to users of prosthetics is a largely unsolved challenge. While past studies using invasive stimulation suggested that sensory feedback may help in handling fragile objects, none explored the underpinning, relearned, motor coordination during grasping. In this study, we aimed at showing for the first time that intraneural sensory feedback of the grip force (GF) improves the sensorimotor control of a transradial amputee controlling a myoelectric prosthesis. Approach . We performed a longitudinal study testing a single subject (clinical trial registration number NCT02848846). A stacking cups test (CUP) performed over two weeks aimed at measuring the subject's ability to finely regulate the GF applied with the prosthesis. A pick and lift test (PLT), performed at the end of the study, measured the level of motor coordination, and whether the subject transferred the motor skills learned in the CUP to an alien task. Main results . The results show that intraneural sensory feedback increases the subject's ability in regulating the GF and allows for improved performance over time. Additionally, the PLT demonstrated that the subject was able to generalize and transfer her manipulation skills to an unknown task and to improve her motor coordination. Significance . Our findings suggest that intraneural sensory feedback holds the potential of restoring functionally effective tactile feedback. This opens up new possibilities to improve the quality of life of amputees using a neural prosthesis.